Study on risk factors of road traffic accident victims attending a tertiary care hospital at Tirupati - P., Shakeer Kahn; N., Bayapa Reddy; K., Ashok Kumar Reddy; G., Ravi Prabhu (International Journal Of Community Medicine And Public Health, 2017)
Background: Road traffic accidents stand as one of the leading causes of mortality and morbidity across the globe. Increase in the number of motor vehicles, poor enforcement of traffic safety regulations, inadequacy of health infrastructure, and poor transport facilities makes the situation still worse. The objective of the study is to know the role of victims and various risk factors related to RTA. To determine the association of risk factors with type of injury and to know the pre-existing medical disorders in RTA victims. Methods: A hospital based, cross sectional study with victims of road traffic accidents admitted in S.V.R.R. Government General Hospital, Tirupati, as study subjects was done during June 2013 to May 2014 for one year where 820 victims of road traffic accidents were interviewed after taking prior consent using a predesigned questionnaire. Results: Most of the victims were drivers (48.5%) followed by passengers (31.7%) and pedestrian (19.8%). No two wheeler driver was wearing helmet. 74% of the four wheeler occupants were not using seat belts. Among drivers and pedestrians, 29.2% were under the influence of alcohol and 12.7% were listening to music. 55.8% of the passengers felt that their vehicle was going with over speed. 17.1% & 11.0% of the participants had history of hypertension and diabetes. Conclusions: There is a need to develop integrated surveillance system to identify the road traffic injury burden and the causal/risk factors. Enforcement of stringent road traffic laws to bring down the burden of road traffic accidents.